Effects of garlic powder and salt additions on fatty acids profile, oxidative status, antioxidant potential and sensory properties of raw and cooked rabbit meat burgers. (November 2020) - Mancini, Simone; Mattioli, Simona; Nuvoloni, Roberta; Pedonese, Francesca; Dal Bosco, Alessandro; Paci, Gisella
Abstract: Rabbit burgers were evaluated for fatty acids profile, oxidative status, antioxidant potential and sensory during storage time of seven days at 4 °C. The aim of the research study was to evaluate if a common culinary spice as garlic could overcome the controversy effects of salt (mostly related to a pro-oxidant effect). Therefore, four formulations were made: only meat (control, C) meat added with garlic powder at 0.25% (G), meat added with salt at 1.00% (S) and meat added with garlic powder (0.25%) and salt (1.00%) (GS). As results, it was highlighted that garlic powder was not capable to reduce significantly the negative effect related to the salt addition. Salt induced different modifications to burgers leading to a more liked product due to its properties to enhance sensory characteristics, on the other hand, induced different oxidation processes that could decrease the nutritional value. Further studies are needed to better elucidate if different garlic products/concentrations could apport higher beneficial effects.